Smurf vs. Smurf - Peyo (Peyo. Smurfs graphic novel, 2012)
"Two sides of the Smurf Village are strongly divided over the Smurf language ... After several failed attempts at peace-making, Papa Smurf sees only one possible solution ... he must turn to the dark side ... and enlist the help of Gargamel!"--Cover.